Guide technique pour les tranferts securises de materiel genetique de cacaoyer. Revision des Directives Techniques FAO/IPGRI No. 20 (Troisième édition, Octobre 2017) - End, M.J.; Daymond, Andrew J.; Hadley, P.; Global Cacao Genetic Resources Network; Bioversity International (2017)
These guidelines describe technical procedures that minimize the risk of pest introductions with movement of cacao germplasm for research, crop improvement, plant breeding, exploration or conservation. The recommendations made in these guidelines are intended for small, specialized consignments used in research programmes, e.g. for collection, conservation and utilization for breeding of plant genetic resources.